INFECTION COMPLICATIONS AFTER COLON-PROCTOLOGIC SURGERIES: EPIDEMIOLOGY, PATHOGENESIS AND PREVENTION - I. V. Shlyk; A. A. Zakharenko; V. A. Panafidina; O. N. Ten (Вестник анестезиологии и реаниматологии)
The review presents some data that reflect the incidence frequency, pathogenesis and approaches to the prevention of infectious complications after coloproctological surgery. They show no uniform recommendations for prevention thereof using the techniques and technologies available with the emergency care specialists. The effectiveness of various pro- and prebiotics, fecal microbiota transplantation are most extensively studied. Also the role of changes in intestinal canal biocenosis and endoluminal translocation in the pathogenesis of systemic infection and other infectious complications is demonstrated.